PENGUJIAN FAMA-FRENCH THREE FACTOR MODEL TERHADAP EXCESS RETURN SAHAM PADA PERUSAHAAN INDEKS KOMPAS100 PERIODE 2016-2020 - FAUDIA RIZKY APRILLIA, - (2021)
This study aims to determine the effect of the Fama French Three Factor Model on the Excess Return of shares in companies included in the KOMPAS100 index list during the 2016-2020 period. The population in this study were 100 companies listed on the KOMPAS100 index. The sample selection in this study used purposive sampling method and obtained a sample of 58 companies. The analytical technique used is Multiple Linear Regression Analysis and there are 6 regression models consisting of portfolio regression BH, BM, BL, SH, SM and SL. The tools used are the Eviews-10 program and Misrosoft Excel 2010. The results show that the Fama French Three Factor Model is able to explain the estimation of excess stock returns well in all portfolios contained in this model.